2011
DOI: 10.1007/s11906-011-0190-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Therapy and Cardiovascular Health

Abstract: Vitamin D belongs to the family of nuclear steroid hormones, which has pleiotropic effects on several organ systems. Different vitamin D compounds have been studied as potential cardioprotective agents over the past 20 years. The results of these clinical studies vary based on the form and dosage of vitamin D administered during the trial. In the past 5 years, many have described an association of vitamin D compounds and cardiovascular health through reduction in blood pressure, reduction in inflammatory bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Optimal vitamin D status is important in patients with CKD to regulate parathyroid hormone (PTH) concentrations [3], [4], [5] for optimal bone health and prevention of osteomalacia and for potential cardioprotective effects [3], [6], [7]. Recent reports have established an association between vitamin D insufficiency and anemia in patients with CKD [8], [9], [10]; however, the role for vitamin D in the regulation of anemia has not been fully explained.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal vitamin D status is important in patients with CKD to regulate parathyroid hormone (PTH) concentrations [3], [4], [5] for optimal bone health and prevention of osteomalacia and for potential cardioprotective effects [3], [6], [7]. Recent reports have established an association between vitamin D insufficiency and anemia in patients with CKD [8], [9], [10]; however, the role for vitamin D in the regulation of anemia has not been fully explained.…”
Section: Introductionmentioning
confidence: 99%
“…Activated T cells increase oxidative stress followed by accelerated angiotensin II secretion [26]. Vitamin D as an anti inflammatory factor can eventually reduce angiotensin II concentration [26,27].…”
Section: Effects Of Vitamin D On Renin-angiotensin System and Blood Pmentioning
confidence: 99%
“…Vitamin D as an anti inflammatory factor can eventually reduce angiotensin II concentration [26,27]. A study on patients with chronic kidney disease reported that treatment with intravenous calcitriol can cause left ventricle hypertrophy regression, plasma rennin activity reduction and angiotensin II level decline [28].…”
Section: Effects Of Vitamin D On Renin-angiotensin System and Blood Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Long term studies of the population of Framingham, MA 3,4 have provided valuable insights into CVD risk, and the Framingham score 3 continues to be a highly useful tool for assessing risk in populations represented by the original Framingham studies. In recent years, several other measures have been proposed for refining the predictive accuracy of the Framingham score, and all require additional laboratory testing, [5][6][7][8] radiographic imaging of the coronary arteries, 9,10 or ultrasound imaging of the carotid arteries. 11,12 While additional refinement of risk is possible with these advanced methodologies, their use in large populations is prohibitive because of cost.…”
Section: Introductionmentioning
confidence: 99%